The Effect of Tax Revenues on Inflation in Selected OECD Countries - Güneş, Hakan; Güneş, Hakan (Ahmet Arif EREN, 2020)
If the seniorage leads revenue through state which can cause inflation at the same time, the expected income growth does not occur because of being delays in tax collection. In countries where the price elasticity of the tax system is less than 1, the Olivera-Tanzi effect, which states that the flaw in tax collection creates inflation and reduces real tax revenues, advocated a negative relationship between tax revenues and inflation. However, the main point here is the real value of taxes. In countries that adopt more liberal policies, the share of tax revenues in GDP is low. In this context, the aim of this study is to examine the effects of tax revenues on inflation in 28 OECD countries for the period 1995-2018 through panel data analysis. In the study, the horizontal cross-section dependency was neglected and first generation panel unit root tests were applied. Since the variables are stationary at the level, the cointegration test that gives the long-term relationship has not been passed. As a result of the Hausman test, it has been determined that the model will be estimated based on random effects. As a result of the study, it was determined that the increasing in tax revenues will increase inflation.
Keywords: [No Keyword]